Tracking IUCN extinction risk at sub-regional scale: lessons from comparing Italian Red List assessments for cartilaginous species within a decade (2013–2022) - Scacco, Umberto; Battistoni, Alessia; Garibaldi, Fulvio; Raicevich, Saša; Rondinini, Carlo; Serena, Fabrizio; Tunesi, Leonardo; Vacchi, Marino; Fortibuoni, Tomaso (Frontiers in Fish Science, 2024)
This brief research report presents the 2022 updated IUCN Red List for the cartilaginous fish fauna (76 species) recorded in the Italian seas and compares it with the 2013 assessment. Overall, the number of Data Deficient (DD) species decreased in favor of both threatened and unthreatened categories. Out of five DD species in the 2013 assessment, three acquired the status of threatened species (Vulnerable or higher) and two an unthreatened (Least Concern or higher) status in the 2022 assessment. Additionally, the classification for one species changed from Least Concern in 2013 to DD in 2022. The comparison between assessments showed no significant change in the average extinction risk status of cartilaginous fish populations of the Italian seas. Even though 2013-DD species decreased in number, the latter still remains high in the updated Italian IUCN Red List assessment. 1 5 Author Contributions US: conceptualization (lead); data curation (lead); formal analysis (lead); investigation (lead); methodology (lead); resources (co-lead); software (lead); supervision (lead); validation (lead); visualization (lead); writing-original draft (lead); writing-review and editing (lead).